Contamination and suitability of soils for growing bio products in Russia - A. L. Ivanov; V. S. Stolbovoy; A. M. Grebennikov; Yu. A. Dukhanin (Бюллетень Почвенного института им. В.В. Докучаева)
The area of impact zones of industrial contamination, oil and oil products spills, motor vehicle emissions, radioactive substances, as well as pesticides and mineral fertilizers application on agricultural lands of the Russian Federation is calculated. The share of the territory under consideration in the total area of agricultural lands of the country does not exceed 3%. Soils in the zone of contamination influence are considered to be potentially polluted and should be included in the monitoring program of agricultural land. Soils outside the zone of influence of pollutant dissemination are uncontaminated. Regular monitoring of contamination of these soils should not be carried out, which will reduce the costs of monitoring. More than 97% of the Russian agricultural land is represented by uncontaminated soils and is suitable for the production of bio products. Regular monitoring of contamination of these soils should not be conducted, which will reduce the cost of the survey, including sample collection, preparation and analysis. In view of the lack of soil contamination, the transition to the cultivation of bio products should be based on declarative approach. In this case, bio production should meet the requirements of special cultivation technologies and the product quality standards.